The fundamental rights of university professors of private universities in employment contracts subject to modality, in the interpretation of the constitutional court - Loaiza, Marco Hernán Pantigozo (Journal of Posthumanism, 2024)
This research examines the conflict between the decisions of the Constitutional Court of Peru and the labor rights of professors hired in private institutions, within the context of the autonomy of universities. The hypothesis is posited that the Court, by prioritizing university standards over the prevailing labor regime, has curtailed the right to work and job security of these educators. The present study employs a qualitative and interpretative approach, drawing upon a comprehensive review of twelve constitutional rulings issued between 2003 and 2013. The Political Constitution, University Laws No. 23733 and No. 30220, as well as Legislative Decree No. 728, are analyzed, in addition to principles such as the supremacy of reality and the safeguard against unjustified dismissals. The results demonstrate a jurisprudence that disregards the distortion of fixed-term contracts, even in circumstances of continuous employment. In the majority of cases, the Court dismissed the applications for amparo submitted by educators, deeming public competition as the sole legitimate avenue for attaining stability. This study finds that the trend in jurisprudence has undermined the protection of fundamental rights under the pretext of university autonomy. It is recommended that a re-evaluation of this position be undertaken, with the objective of achieving a harmonious equilibrium between the interests of academic institutions and those of labor rights.